KNOWLEDGE PRODUCTION IN SPORT MANAGEMENT IN FEEVALE UNIVERSITY, NOVO HAMBURGO – RS:A STUDY ON THE TRAJECTORY AND COMPOSITION OF PAPERS. (Fiep Bulletin - online, 2012)
The aim of the study was to describe the trajectory and composition of knowledge in sport management, starting from the constitution of research groups and Final Papers in Undergraduate and Specialization courses, in Feevale University, in Novo Hamburgo - RS. It is attempted, specifically, to determine the fields of concentration of management on which the papers were produced, their development through the years and on what undergraduate courses papers on this field are concentrated. The knowledge area of management has been having a significant scientific production in Brazil in the last decades, a fact which does not happen with the specific field of study that deals with sport management, physical exercise and leisure, in spite of the recent growth. The study is of a descriptive type. As a source for data collection the titles available in the collection of University Feevale library were selected by consulting the online system, using the key words: sport management; sport; and sport administration. Descriptive statistics was used for the handling of data, verifying frequency, percentage and standard deviation. The results pointed that the papers had an increase and constancy of production in the field of study from 2007 on, considering that the year 2010 is the one which shows a higher number of papers, with 21,62% of the total papers carried out; there is a significant production in the field of Marketing with 40,54% of the papers done; and the greater concentration of papers happened in the Business Administration course, 32,43%, followed by the Physical Education course with 24,32% of the papers. Therefore, one concludes that there is a relative increase in papers and a significant volume from 2007 on, which coincides with the advance in Sport Management and, also, with the inclusion of the research area in Feevale University.
Keywords: Knowledge production; Sport management; Administration